Using Raman spectroscopy and an exponential equation approach to detect adulteration of olive oil with rapeseed and corn oil. (15th December 2020) - de Lima, Thaís Karine; Musso, M.; Bertoldo Menezes, D.
Highlights: Detecting and quantifying olive oil adulteration by Raman spectroscopy. Appling an exponential equation for quantification the adulteration of olive oil with rapeseed oil or corn oil. Proposing a new method to analyse adulteration of foods based on Raman spectroscopy and exponential equation. Abstract: This study presents a method to determine adulteration of olive oil (obtained from Olea europea, i.e. olives) with rapeseed oil (obtained from Brassica napus ) or with corn oil (also named maize oil, obtained from Zea mays, i.e. maize) using Raman spectroscopy and a mathematical method based on exponential equation fit. The samples were prepared by mixing olive oil with volume fractions (0–100%) of rapeseed or corn oil. The oils were differentiated spectroscopically using intensity ratio for specific Raman peaks; Raman spectroscopy is able to detect changes within a liquid molecular environment without the need for sample treatment. It was possible to determine rapeseed or corn oil volume fractions added into the olive oil using the method proposed. Thus, the potential of Raman spectroscopy as a technique for determining adulteration of olive oil was corroborated clearly, opening the potential to investigate adulteration of other liquid foods, without any need for sample preparation.